Age-related macular degeneration: current treatments - Jean Pierre Hubschman (Dove Medical Press, 2009)
Jean Pierre Hubschman, Shantan Reddy, Steven D SchwartzJules Stein Eye Institute, Department of Ophthalmology, University of California, David Geffen School of Medicine, Los Angeles, California, USAPurpose: Although important progress has been made in understanding age-related macular degeneration (AMD), management of the disease continues to be a challenge. AMD research has led to a widening of available treatment options and improved prognostic perspectives. This essay reviews these treatment options.Design: Interpretative essay.Methods: Literature review and interpretation.Results: Current treatments to preserve vision in patients with non-exudative AMD include antioxidant vitamins and mineral supplementations. Exudative AMD is currently most often treated monthly with anti-VEGF intra-vitreal injections. However, investigators are beginning to experiment with combination therapy and surgical approaches in an attempt to limit the number of treatment and reduce the financial burden on the health care system.Conclusion: By better understanding the basis and pathogenesis of AMD, newer therapies will continue to be developed that target specific pathways in patients with AMD, with the hoped for outcome of better management of the disease and improved visual acuity.Keywords: age-related macular degeneration, VEGF, photodynamic therapy, laser, surgery